Comparative Analysis of Intensive Care Prognosis Scoring Systems and Acute Kidney Injury Scores (AKIN and pRIFLE) in Critically Ill Children - Ayben Leblebici; Gurkan Bozan; Asli Kavaz Tufan; Eylem Kiral; Ebru Kacmaz; Ener Cagri Dinleyici (MDPI AG, 2023)
The development of AKI (acute kidney injury) in critically ill patients in pediatric intensive care units (PICUs) is one of the most important factors affecting mortality. There are scoring modalities used to predict mortality in PICUs. We compared the AKIN (Acute Kidney Injury Network) and pRIFLE (pediatric risk, injury, failure, loss, and end stage) AKI classifications and PICU scoring modalities in this study. Methods: A total of 716 children, whose serum creatinine levels were within the normal limits at the time of admission to the PICU between January 2018 and December 2020, were included. Along with the demographic and clinical variables, AKIN and pRIFLE classifications were recorded at the most advanced stage of AKI. Along with the PIM-2, PRISM III, and PELOD-2 scores, the highest value of the pSOFA score was recorded. Results: According to the pRIFLE and AKIN classifications, 62 (8.7%) patients developed kidney injury, which had a statistically significant effect on mortality. The occurrence of renal injury was found to be statistically strongly and significantly correlated with high PRISM III, PELOD-2, and pSOFA scores. When the stages of kidney injury according to the AKIN criteria were compared with the PRISM III, PELOD 2, and pSOFA scores, a significant difference was found between the patients who did not develop AKI and those who developed stage 1, stage 2, and stage 3 kidney injury. For the PRISM III, PELOD 2, and pSOFA scores, there were no significant differences between the stages according to the AKIN criteria. A substantial difference was discovered between the patients who did not develop AKI and those who were in the risk, injury, and failure plus loss stages according to the pRIFLE criteria. According to the PIM-2 ratio and pRIFLE criteria, there was a statistically significant difference between patients in the injury and failure plus loss stages and those who did not develop AKI. Conclusions: Our study is the first pediatric study to show a substantial correlation between the variables associated with the PICU scoring modalities in critically ill children with AKI. Identifying the risk factors for the development of AKI and planning antimicrobial regimens for patients with favorable prognoses at the time of PICU admission could lower mortality rates.